Boosting performance of CdTe photocathode with pulse-reverse electrodeposited nickel telluride-nickel phosphide dual co-catalysts. (22nd February 2023) - Jo, Woohyeon; Han, Seungyeon; Jeong, Jaebum; Kim, Taegeon; Son, Min-Kyu; Yoon, Seog-Young; Jung, Hyunsung
Abstract: Herein, noble-metal free Ni–Te/Ni–P dual co-catalysts are investigated as attractive candidates for improving the photoelectrochemical (PEC) performance of CdTe photocathodes. The Ni–Te/Ni–P dual co-catalysts are deposited on CdTe photocathodes via pulse-reverse electrodeposition and post annealing. The Ni–Te/Ni–P catalyzed CdTe photocathodes show a remarkable PEC performance, especially in terms of the photocurrent density, which is approximately 11.06 times higher than that of the pristine CdTe photocathode. The Ni–Te/Ni–P dual co-catalysts boost the catalytic activity via enhanced charge transfer and surface reaction kinetics. The photogenerated electrons and holes are effectively separated by the Schottky contact between the Ni–Te/Ni–P dual co-catalysts and the CdTe absorbing layer. Thus, the rational design of the CdTe photocathode with the Ni–Te/Ni–P dual co-catalysts can dramatically enhance the PEC performance of the CdTe photocathodes.